Fluorescence anisotropy using highly polarized emitting dyes confined inside BNNTs. Issue 3 (16th January 2023) - Badon, A.; Marceau, J.-B.; Allard, C.; Fossard, F.; Loiseau, A.; Cognet, L.; Flahaut, E.; Recher, G.; Izard, N.; Martel, R.; Gaufrès, E.
Abstract : Fluorescence anisotropy from 6T organic emitters aligned inside boron nitride nanotubes, themselves aligned in a polymeric matrix. Abstract : Polarized fluorescence emission of nanoscale emitters has been extensively studied for applications such as bioimaging, displays, and optical communication. Extending the polarization properties in large assemblies of compact emitters is, however, challenging because of self-aggregation processes, which can induce depolarization effects, quenching, and cancellations of molecular dipoles. Here we use α-sexithiophene (6T) molecules confined inside boron nitride nanotubes (6T@BNNTs) to induce fluorescence anisotropy in a transparent host. The experiments first indicate that individual 6T@BNNTs exhibit a high polarization extinction ratio, up to 700, at room temperature. Using aberration-corrected HRTEM, we show that the fluorescence anisotropy is consistent with a general alignment of encapsulated 6T molecules along the nanotube axis. The molecular alignment is weakly influenced by the nanotube diameter, a phenomenon ascribed to stronger molecule-to-sidewall interactions compared to intermolecular interactions. By stretching a flexible thin film made of transparent polymers mixed with 6T@BNNTs, we induce a macroscopic fluorescence anisotropy within the film. This work demonstrates that the dyes@BNNT system can be used as an easy-to-handle platform to induce fluorescence anisotropy in photonic materials.